PENTINGNYA PERLINDUNGAN DAN KEAMANAN DATA PRIVASI DI ERA DIGITAL - Abelia Mita Baqis; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
The rapid advancement of information technology has transformed personal data into a valuable yet highly vulnerable asset,particularly susceptible to breaches and misuse. Information such as names, addresses, contact numbers, and financial data are increasingly accessible and illegally utilized. This condition demands more secure and structured information protection and management. This article discusses the importance of personal data security, the challenges that exist, and the strategic solutions that can be implemented. The research was conducted using a qualitative method through literature studies from various relevant sources. The analysis shows that there is a need to increase awareness and implement a reliable digital security system by individuals and institutions to reduce the risk of information leakage and misuse.